Pengaruh Perlindungan Sosial Terhadap Kesejahteraan Masyarakat Jawa Timur Menggunakan PLS-SEM - Putri, Fitriani Aditya; Nursiyono, Joko Ade (Seminar Nasional Official Statistics, 2025)
Various social protection programs have been launched by both the East Java Provincial Government and the Central Government. However, social protection programs have not been optimal in reducing poverty rates and improving people's welfare in East Java. Based on the measurement of the Social Protection Index (IPS) of districts and cities from the dimensions of depth, coverage, and impact, the results show that the quality of the Social Protection Index (IPS) in East Java in 2022 is quite good. The highest IPS figures in 2022 were achieved by Pamekasan Regency, Probolinggo Regency, and Ponorogo Regency. These three regions have the highest IPS in 2022 because each region has a dominant dimension value. In addition, based on the results of the Partial Least Square Structural Equation Model (PLS-SEM) analysis, it was found that social protection has a significant effect on economic aspects, health aspects, and safety aspects. In order to improve the welfare of the people of East Java, the central government and regional governments are expected to optimize government spending on the Kartu Indonesia Sehat and beneficiary families (economic aspect), allocate a budget in the health sector for the prevention of Dengue Fever and Malaria (health aspect), and provide work accident insurance for all workers (safety aspect).